IMPROVEMENT OF MANAGEMENT OF FINANCIAL RESOURCES AS PRECONDITION OF EFFECTIVE ACTIVITY OF STATE AGRICULTURAL ENTERPRISES - Halaiko, Andrii (Social Economics, 2019)
The article deals with the determination of directions of improvement of management of the cash funds of the state agricultural companies. The research is started with determination of relevance and necessity of finding ways to improve management of the cash funds of the state economic entities in agriculture. According to conducted research, the following directions of improvement of management the financial resources of the state agricultural enterprises are established: impartial and timely analysis of financial results; optimization of products structure; adherence of complex-system approach in the management of the cash funds; improvement of financial planning and budgeting; rational management by fixed assets and by working capital; taking into account reserves of reducing of cost of the products; application rational system of the management of financial flows; delegating functions of book-keeping and financial management of small state agricultural enterprises to consulting firms; maximal harmonization of functioning of financial and organizational structure; increase financial potential by increasing profit and solvency; planning cash receipts, priority payments, budget subdivisions of the enterprise, conducting payment calendars; daily distribution of the financial resources which arrived according to beforehand determined priorities, drafting plans of move of cash funds per by subdivisions of the enterprise. The article determines the unprofitability of the state agricultural enterprises as their main problem. The research proposes to eliminate unprofitability of the state companies in the agriculture under conditions of selling of the state agricultural products below of break-even point and in case of falling prices for these products. In further research, it is necessary to determine the ways of profitability increase of the state agricultural enterprises without production diversification.